O HUMOR COMO RECURSO LINGÜÍSTICO: UM ESTUDO DE ENSAIO JORNALÍSTICO PUBLICADO EM REVISTA SEMANAL - Barcelllos, Any Lílian Maxemiuc (Intercâmbio, 2010)
The present study consists of a case study based on an essay written by a journalist in a weekly magazine. The analysis of the elements present in the interpersonal metafunction shows the strategies used by the writer to persuade readers about his point of view. Context and intertext support the understanding of humour present in the essays.